PENGARUH SOSIAL MEDIA TERHADAP MITIGASI BENCANA BANJIR - Sintiya, Aqilla Sintiya; Rahma, Najahaura; Siregar, Ummi Kalsum (Universitas Insan Pembangunan Indonesia, 2024)
Indonesia frequently experiences natural disasters, especially floods. The National Disaster Management Agency (BNPB) utilizes social media to reduce the likelihood of disasters and disseminate information about them. Disaster mitigation is an effort to reduce the risks and impacts of disasters on communities in disaster-prone areas. These disasters can include natural events such as earthquakes, tsunamis, floods, or volcanic eruptions, as well as human-induced disasters such as social conflicts and terrorism. The goal of disaster mitigation is to minimize the risk of fatalities and injuries to residents and reduce losses when hazards occur in the future. This includes mitigating economic losses and damage to public sector infrastructure. The objective of this study is to gain an understanding of how social media can be leveraged to disseminate information about natural disasters and to build public awareness regarding potential disaster risks in the future.Keywords:Disaster mitigation, Floods, Social media, Impact, Society